Consecutive oxidative additions of iodine on undulating 2D coordination polymers: formation of I–Pt–I chains and inhomogeneous layers. Issue 21 (14th January 2019) - Ohtani, Ryo; Yamamoto, Riho; Ohtsu, Hiroyoshi; Kawano, Masaki; Pirillo, Jenny; Hijikata, Yuh; Sadakiyo, Masaaki; Lindoy, Leonard F.; Hayami, Shinya
Abstract : Consecutive oxidative additions of iodine on the undulating 2D coordination polymer produced unprecedented anisotropic structures. Abstract : The 2D coordination polymers, [Mn(salen)]2 [Pt II (CN)4 ]1− x [Pt IV (CN)4 (I2 )] x (salen = N, N' -ethylenebis(salicylideneaminato), x = 0.18 (1 ), 0.45 (2 ), 0.85 (3 )), have been synthesized via consecutive oxidative additions of iodine to the 2D undulating layers in [Mn(salen)]2 [Pt II (CN)4 ]. The presence of I–Pt–I chains perpendicular to the layers and the inhomogeneity of individual I–Pt–I sites were demonstrated. The I–Pt–I chains in3 give rise to an absorption band involving the excitation that arises from an antibonding nature orbital to the corresponding bonding nature orbital between iodides in the I–Pt–I bridging units. Moreover, variable-temperature X-ray powder diffraction patterns and Raman spectra for1 and2 indicate that some I–Pt–I sites display different vibrational energies that are associated with the contraction of the zigzag 2D layers.